Analisi Historis Kain Songket “Motif Manuk” di Kabupaten Manggarai Barat - Faizah Ulumi Firdausi; Hendri Setiawan (IKIP Budi Utomo Malang, 2022)
Songket weaving with the Mata Manuk motif is a rare human creation that has a high philosophical value. The philosophy of the mata manuk motif is taken from the worship that is practiced in every tradition in West Manggarai, until finally it is poured into a work of art that has a high value. The attention motif can be a symbol of female eyes implying that women have sharp eyes, have central eyes, conscience eyes and therefore body eyes. The symbols contained in the eye manuk motif are graceful and authoritative for the people who use them historically have a high meaning in human life, especially the West Manggarai Community. The research location is Nangalili Village, Lembor District, East Nusa Tenggara. This study aims to identify and explain the history of the songke sarong motif. The research method used can be a qualitative method. the topic of this research is 5 people, namely 3 people from the first community of Nangalili Village who are sheltered in Nangalili village, and several students of IKIP BUDI UTOMO Malang who are in the Nangalili village environment. Data collection techniques during this study used data analysis techniques, and the supporting method techniques were interviews and documentation. The results showed that the factor of ignorance of the meaning of the songke sarong motif was due to not understanding.